Pseudodifferential calculus on a singular foliation - Iakovos Androulidakis; Georges Skandalis (J. Noncommut. Geom., 2011)
In a previous paper ([1]), we associated a holonomy groupoid and a C*-algebra to any singular foliation (M,ℱ). Using these, we construct the associated pseudodifferential calculus. This calculus gives meaning to a Laplace operator of any singular foliation ℱ on a compact manifold M, and we show that it can be naturally understood as a positive, unbounded, self-adjoint operator on L2(M).